Changes in primary healthcare workforce burnout during and after the termination of COVID-19 emergency response: A one-and-half-year observational study - Xueji Wu; Huihong Ruan; Xiaoying Feng; Chaojun Xie; Ronald R. O’Donnell; Zhoubin Zhang (Journal of Family Medicine and Primary Care)
Background: Primary healthcare workforce (PHCW) should be suffered from less burnout after the termination of the COVID-19 response. The current study compared the changes in the three dimensions of burnout in PHCW during and after the response. Methods: Two convenience-sampling, online, cross-sectional questionnaire studies were conducted in local PHCW. Studies were administered in April 2022 and 8 months after the termination. Burnout was measured by the Chinese version of 15-item Maslach Burnout Inventory-General Survey, which assesses three dimensions: emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (reduced PA). The primary outcome was the prevalence of its three dimensions. Data on demographics, work environment, health conditions, and outlets for stress reduction were collected. We compared burnout and associated factors between the study periods by using Student’s t-test, Chi test, or Mann‒Whitney test. The association between factors and burnout was identified by a logistic regression model. Results: In total, 162 and 200 participants completed the questionnaires during and after the response. No significant differences in demographics, including age, gender, education attainment, work experience, or seniority level were observed. The prevalence of burnout-free status was similar (9.9% vs 12.5%, P = 0.434) between the two periods. Severe burnout decreased from 45.7% to 0%, and moderate burnout nearly doubled after the response. The prevalence of EE decreased the most, by 55.0%, followed by that of DP, which decreased by 38.4% (all P < 0.001); however, there was no difference in the prevalence of reduced PA (77.2% vs 74.5%, P = 0.557). Logistic regression showed that promotion and alcohol consumption decreased the risk of EE. Considering leaving the job increases the risk of DP, a lower self-evaluated health score and more distress were associated with EE and DP. Exercise decreased the risk of reduced PA. Conclusions: Inconsistent with the hypothesis, we found that severe burnout decreased, but moderate burnout increased in PHCWs after the response. EE and DP decreased more, but reduced PA had no change. Incentives, improved self-evaluated health conditions, alcohol consumption, and exercise ameliorate burnout. Healthcare policy makers must consider multiple effective ways to mitigate burnout in the post-epidemic era.